2021
DOI: 10.1155/2021/7423101
|View full text |Cite|
|
Sign up to set email alerts
|

To Explore the Haemostatic Effect of Compression Haemostasis Using an Ultrasonic Probe under the Guidance of Ultrasound after Radial Artery Puncture

Abstract: Objective. To evaluate a new haemostasis method using an ultrasound probe to compress the radial artery and haemostasis under direct vision to replace traditional manual compression of the radial artery. Methods. According to a random number table, 240 patients with gastrointestinal tumours who had undergone arterial puncture were divided into Group A (120 cases) and Group B (120 cases). In Group A, patients were under the guidance of ultrasound to confirm the vascular port, determine the compression position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…
This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:
…”
mentioning
confidence: 99%